We have the line x = 42 - 14y. The other line is y = 2x - 11.

Use x = 42 - 14y from the equation of the first line and substitute in the second

y = 2x - 11

=> y = 2( 42 - 14y) - 11

...

## Unlock

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

We have the line x = 42 - 14y. The other line is y = 2x - 11.

Use x = 42 - 14y from the equation of the first line and substitute in the second

y = 2x - 11

=> y = 2( 42 - 14y) - 11

=> y = 84 - 28y - 11

=> y = -28y + 73

=> 29y = 73

=> y = 73/29

x = 42 - 14 * ( 73/29)

=> x = 196/29

**Therefore, the lines do intersect and the point of intersection is (196/29 , 73/29)**